Orientalism and the Challenge to the Originality of the Al-Qur'an Lexicon: A Critical Study of Western Philological Approaches - Mufrodi Mufrodi; Subhan Subhan; Zaki Ghufron; Dedi Sunardi (ADP Publisher, 2024)
This study critically examines the philological and historical-comparative linguistic approaches developed by Western orientalists in analyzing the Qur'anic lexicon and their implications for the doctrine of the authenticity and purity of the language of revelation in Islam. It also explores Muslim scholars' responses to claims of foreign language influence in the lexical construction of the sacred text. Starting from the assumption that the Qur'an contains elements of Aramaic, Hebrew, Syriac, and Ethiopic languages, orientalists such as Theodor Nöodeke, Abraham Geiger, Arthur Jeffery, and Christoph Luxenberg attempted to interpret the Qur'anic text as an evolutive product of pre-Islamic Arabic culture and history. This approach, despite its contribution to the field of language history, has been criticized by Muslim scholars for ignoring the theological dimension and sacredness of the Qur'an as divine revelation. Using a qualitative method and a desk study approach, this research analyzes key works from both orientalists and Muslim scholars. The results show that Western philological approaches to the Qur'an are not scientifically neutral but contain historical-critical assumptions that often contradict the normative-transcendental approach in the Islamic tradition. In response, contemporary Muslim scholars have developed an integrative approach that balances linguistic studies with contextual interpretation and emphasizes the importance of taking into account the dynamics of classical Arabic, Qur'anic rhetorical structures, and the context of revelation. As such, this study affirms the importance of a multidisciplinary and dialogical approach in understanding the complexity of Qur'anic vocabulary in order to avoid methodological reductionism and maintain the epistemic integrity of the revealed text.